Reasons, Answers, and Goals - Turri, John (Journal of moral philosophy, 2012)
I discuss two arguments against the view that reasons are propositions. I consider responses to each argument, including recent responses due to Mark Schroeder, and suggest further responses of my own. In each case, the discussion proceeds by comparing reasons to answers and goals.